Ultrasonic wave effects on the diameter of TiO2 nanoparticles - Hossain Milani Moghaddam; Shahruz Nasirian (South African Journal of Science)
Titanium dioxide (TiO2) nanostructured materials have attracted a great deal of attention because of their numerous applications. However, TiO2 applications depend strongly on the material's high homogeneity and definite phase composition, morphology, particle size, high surface area and porosity, which are dependent on the sample history, the method of preparation and heat treatment. We synthesised TiO2 nanopowder with an anatase structure by the sol-gel method using TiCl4-ethanol solution as a precursor in an argon gas environment, with and without applying ultrasonic waves. Our results show that the use of ultrasonic waves (after aging) has a significant effect on the homogeneity and size of TiO2 nanoparticles. A smaller crystallite size was obtained using ultrasonic waves. For this purpose, the average diameter of TiO2 nanoparticles was decreased by about 3 nm. The synthesised powder was characterised by X-ray diffraction, scanning electron microscopy and transmission electron microscopy.